Pemanfaatan Teknologi Informasi untuk Optimalisasi Dakwah Bagi Kader Nasyiatul Aisyiyah Bulakamba-Brebes - Dyah Apriliani; Ginanjar Wiro Sasmito; Hepatika Zidny Ilmadina (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
Da'wah activities carried out "traditionally" have proven to be an intermediary tool for all people who wish to study and even deepen the religion of Islam. However, along with the development of information technology and the support of the internet, da'wah activities are presented in different ways / methods. These activities are channeled quickly using various online media platforms (in the network) such as preaching through video streaming, via YouTube, through social media (Twitter, Instagram, Facebook, and others) which can be watched repeatedly with large audiences. One of the uses of technology in preaching activities can be done by using smartphones in making interesting multimedia as a medium of preaching. Based on observations in the field, several problems faced by cadres Nasyiatul Aisyiyah Bulakamba-Brebes are that they do not have the understanding and use of information technology in supporting da'wah activities. Therefore, material is given about the importance of using information technology as a medium for da'wah in the era of the industrial revolution 4.0 as well as providing assistance in training in making da'wah media in the form of posters using the Canvas application and video editing using Kine Master. With this activity, the motivation, knowledge, and skills of Nasyiatul Aisyiyah Bulakamba-Brebes cadres in optimizing the use of information technology in da'wah activities will increase.